Normas de comportamiento para mejorar la convivencia intra-clase en los estudiantes de cuarto grado paralelo a de la escuela de educación básica Lauro Damerval Ayora N° 2, de la ciudad de Loja. Periodo 2014- 2015 - Cueva Jara, Tania Maricela (2016)
This research titled RULES OF CONDUCT FOR IMPROVED INTRA-CLASS coexistence in fourth graders PARALLEL TO SCHOOL EDUCATION BACKGROUND LAURO Damerval AYORA No. 2, CITY OF LOJA. PERIOD 2014- 2015, had as its overall objective to apply the rules of behavior to improve intra-class coexistence. The research was pre-experimental and cross-sectional, explanatory character and field; in which methods were used: synthetic, inductive-deductive analytic and statistical- descriptive; the techniques used and the recruitment and survey through its instrument the questionnaire applied to 17 students and a teacher. After obtaining the results showed that most students did not meet the performance standards set out in the classroom, which generated a conflictive coexistence, showing aggressive actions and little companionship. Since the implementation of the workshops was succeeded in establishing student assertive behaviors, which allowed increase fellowship and strengthen the practice of values in the classroom. Thus it was concluded that the application of rules of behavior in the classroom, proved to be one of the most efficient ways to achieve good coexistence through compliance intra behavior. Therefore the teacher is recommended strategies and innovative activities that allow the student to live among peers, putting into practice the values inside and outside the classroom